The Impact Of Telemedicine On Pediatric Emergency Care: Current Trends And Future Directions - Mutlaq Ateeq Mutlaq Alsolami, ‏ Essa Ali Essa Alharthy, ‏ Abdullah Ali M. Atoodi, Haya Hefdallah Hassan Ezadeen, Meshal Salem Ahmed Bajoned, Saeed Moshref Alshehri, Ahmad Ismail Gholam (Journal of International Crisis and Risk Communication Research, 2024)
Background: Telemedicine consultations are bringing specialists virtually into emergency departments in the care of severely ill children that potentially reduce unnecessary transference by facilitating the pediatric professionals to virtually analyse the patients and making precise recommendations. The aim of the study is to analyse the impact of telemedicine on Pediatric emergency care concerning current trends and future directions. The first objective is to analyse the efficiency of telemedicine in pediatric emergency care considering current trends. The second objective of the study focuses on evaluating the challenges of telemedicine in pediatric emergency care. The third research objectives explore future innovations and directions of telemedicine in pediatric emergency care. Methods: A mixed research approach has been used in the study. In this research, a systematic literature review has been conducted on 4 peer conducted on 4 peer review journals. Moreover, a semi-structured survey also has been conducted with 10 pediatricians provides emergency care. In addition, in pediatric emergency care, application of telemedicine is gaining immense prominence. Results: From the thematic analysis, it is found that there are various benefits and challenges of considering telemedicines in pediatric emergency care. The survey revealed that telemedicine has been effective in enhancing efficiency in pediatric emergency care. The healthcare professionals and clinicians are confident in using telemedicine. It is recommended that improving technological infrastructure and increasing pediatric training for care providers in healthcare is essential for further betterment of telemedicine in pediatric emergency care. Conclusion: Telemedicine interventions are found effective in terms of pediatric emergency care delivery. There are advantages with the application of this technology like safest and timely management, convenience, low cost and others. However, there have been critical challenges as well including lack of familiarity, lack of buy-in, technological glitches and others.